Avaliação Comparativa da Agressividade de Meloidogyne javanica e M. incognita à Variedade SP 911049 de Cana-de-açúcar - Barbosa, Bruno F.F.; dos Santos, Jaime M.; Soares, Pedro L.M.; Barbosa, Jose C. (My University, 2009)
Nematodes cause extensive losses to sugarcane in Brazil and also in other producing regions. Meloidogyne incognita, M. javanica and Pratylenchus zeae are the key species for this culture worldwide. In the present study, the aggressiveness of M. javanica and M. incognita to sugarcane variety SP 911049 was evaluated comparatively,. The following parameters were compared: reproduction factor (RF) of these nematodes, effect of nematodes in the natural incidence of pests, and the influence on the development and technological characteristics of sugarcane. Considering the data of RF, biometrics, natural infestation of pests, mortality of plants, and technological variables, it was concluded that M. javanica was more aggressive to sugarcane, although its rate of multiplication was much smaller than the one of M. incognita.
Evaluation of comparative aggressiveness of Meloidogyne javanica and M. incognita on sugarcane variety SP 911049.